The PGRS Domain from PE_PGRS33 of Mycobacterium tuberculosis is Target of Humoral Immune Response in Mice and Humans - Cohen, Ingrid; Parada, Cristina; Acosta-Gío, Enrique; Espitia, Clara (Frontiers in Immunology, 2014)
The PE_PGRS33 protein is a member of the PE family which encompasses the PE and the PE_PGRS subfamilies. Among PE_PGRS´s, this protein is one of the most studied antigen and their immunomodulatory properties are influenced by its PE and PGRS domains. However, the contribution of these domains to the host immune recognition of the PE_PGRS33 protein and their potential role in latent tuberculosis infection in humans is still unknown. In this study, the immunogenic properties of the complete PE_PGRS33 protein and each separately domain were evaluated in BALB/c mice and latent tuberculosis infected humans. In mice, PE_PGRS33 and its domains induced similar antibody production and secretion of IFN-PE_PGRS33 and the PE domain stimulated higher CD4+ and CD8+ T-cell proliferation compared to the PGRS domain. This demonstrated that the principal difference in the immune recognition of the domains is the higher activation of T-cell subpopulations involved in the control of tuberculosis. In humans, the secretion of IFN- in response to PE_PGRS33 was detected in both latent tuberculosis infected and in non-infected vaccinated individuals. The same was observed for antibody response which targets epitopes located in the PGRS domain but not in the PE domain. These observations suggest that T and B cell responses to PE_PGRS33 are induced by BCG vaccination and can be maintained for many years in non-infected individuals. This also indicates that the IFN- response detected might not be associated with latent tuberculosis infection. These results contribute to the elucidation of the role of the PE_PGRS33 protein and its PE and PGRS domains in the immune response against Mycobacterium tuberculosis.